Isolation and characterization of outer and inner membranes of Selenomonas ruminantium: lipid compositions. - Kamio, Y (1980)
The isolation procedure and characterization of the outer and inner membranes from Selenomonas ruminatium cells, a strictly anaerobic bacterium, are described. The metabolic fate of [14C]decanoate incorporated into the outer and inner membranes was examined. The percent distribution of radioactivities in the outer and inner membranes was about 40 and 50% of the total incorporated activity, respectively. Approximately 47% of the radioactivity incorporated into the outer membrane was recovered in the phospholipid fraction, and the remaining radioactivity was found in both aqueous and phenol layers when the outer membrane was treated with phenol-water. In contrast to [14C]decanoate, the percent distribution of [3H]glycerol in the outer and inner membranes was about 25 and 70% of the total incorporated activity, respectively. Most of the assimilated 3H was located in the phospholipid fraction of both membranes. However, no significant label was detected in either the protein or cell wall fraction. The following observations were made concerning lipid compositions in the outer and inner membranes by chemical and isotopic analyses. (i) The outer and inner membranes contained no detectable phosphatidyl glycerol or cardiolipin. (ii) A prominent radioactive compound, designated band III lipid, was found mainly in the outer membrane as a major radioactive spot when cells were grown with [14C]decanoate. This lipid contained phosphorus, 2-keto-3-deoxyoctulosonic acid and 3-OH fatty acid but no detectable glycerol. This lipid was identified tentatively to be 2-keto-3-deoxyoctulosonic acid-lipid A. (iii) Although the ubiquity of phosphatidyl ethanolamine plasmalogen in both outer and inner membranes was confirmed, the occurrence of the molecular species of phosphatidyl ethanolamine plasmalogen was quite different in the outer and inner membranes.